PENGARUH MEDIA VIDEO EDUKASI TERHADAP PENGETAHUAN REMAJA PUTRI TENTANG KANKER PAYUDARA DI SMA NEGERI 9 KOTA BENGKULU TAHUN 2024 - Oktariani, Atika Oktariani (JURNAL BESUREK JIDAN, 2025)
Breast cancer is a malignant tumor that attacks and grows in the breast tissue. Breast cancer is a mass or lump that can spread to other organs and can cause death in women. One of the causes of the still high rate of breast cancer in women is a lack of knowledge and low public awareness about breast cancer prevention, causing this disease to be discovered by ignorance and is already at an advanced stage. This spread is called metastasis. The aim of this research is to understand or find out the influence of educational video media on young women's knowledge about breast cancer in efforts to prevent breast cancer at SMA Negeri 9 Bengkulu City. Method: This research uses a pre-experimental type with a one group pretest-posttest design. This research was conducted at SMA Negeri 9 Bengkulu City from 22-29 April 2024. The sample consisted of 36 young women in class X Science and Social Sciences, using a stratified random sampling technique. Data analysis used the paired T-Test.Result and Discussion: Based on the paired T-Test test, the P-value = 0.000 < 0.05, which means there is a significant influence of education using video media in increasing the knowledge of young women in efforts to prevent breast cancer at SMA Negeri 9 Bengkulu City.Conclusion: Providing education using animated video media has an effect in increasing young women's knowledge about breast cancer. It is hoped that SMA Negeri 9 can utilize educational video media as an alternative in providing education to young women.